Characteristic of correlation between post-stroke spasticity and clinical and paraclinical features of ischemic stroke - Паєнок, Анжеліка Володимирівна; Мітельман, Ірина Миколаївна (ScienceRise: Medical Science, 2016)
The aim of research was to study the correlation between the intense of post-stroke spasticity and certain clinical (severity of stroke in most acute period, pathogenetic subtype of stroke, localization of ischemia zone) and paraclinical )sex, smoking in anamnesis, content of exciting and braking neurotransmitters) factors. Methods. The research included 97 patients with the first ischemic stroke. During the 6th month patients were divided in 2 groups: the ones with post-stroke spasticity and without it. For determination of reliable correlation between the intensity of spasticity and clinical and paraclinical factors the non-parametric correlation coefficient of Kendall range (τ) was used. Results. In the research we observed the reliable positive correlation between spasticity after stroke and the severity degree of ischemic stroke, smoking in anamnesis, localization of stroke in carotid basin and the level of glutamate and aspartate in the most acute period of stroke. It was also revealed the negative correlation of the middle force between the spasticity intensity and glycine and taurine content in the most acute period of ischemic stroke. Conclusions. The revealed correlations between the spasticity degree and clinical and paraclinical parameters can be further used for elaborations of development predicators of spastics and the study of preventive treatment